Pakistan : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2020)
This paper highlights Pakistan's Request for Purchase Under the Rapid Financing Instrument (RFI). With the near-term outlook deteriorating sharply, the authorities have swiftly put in place measures to contain the impact of the shock and support economic activity. Crucially, health spending has been increased and social support strengthened. While uncertainty remains high, the near-term economic impact of coronavirus disease 2019 is expected to be significant, giving rise to large fiscal and external financing needs. The IMF support will help to provide a backstop against the decline in international reserves and provide financing to the budget for targeted and temporary spending increases aimed at containing the pandemic and mitigating its economic impact. In response to the crisis, the government of Pakistan has taken swift action to halt the community spread of the virus and introduced an economic stimulus package aimed at accommodating the spending needed to tackle the health emergency and supporting economic activity.